Studi Eksplorasi Kesiapan Internasionalisasi Warung Kopi di Kota Banda Aceh ke ASEAN - Ferdi Nazirun Sijabat; Muhammad Muhammad (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims at exploring and understanding two areas: 1. The readiness of coffee shops entrepreneurs in Banda Aceh to expand their business into ASEAN market. 2. Assessing the strength, weakness, opportinty and threat of the coffee shops indusry in Banda Aceh. This study employed exploratory qualitative methode by conducting interview to four key persons who own and manage the coffee shops. The study found that in regards with internationalization of coffee shops, there are three categories : 1. Not willing to internationalize and not ready; 2. There is intention, yet not ready, 3. Ready to internationalize but lack of suitable business partner. This study also provide the SWOT of the coffee shops in Banda Aceh. The implication of this study is that: 1). It is necessary for Provincial Government of Aceh to provide training for coffee shops managers/owners in order to increase their readiness and enable them to find suitable business partner for internationalizing their business into ASEAN market. 2). Future study can be conducted using another type of quantitative or qualitative method, so that the findings can be validated and generalized.